Electron irradiation effects on lithium peroxide. (13th February 2018) - Kikkawa, Jun; Shiotsuki, Taishi; Shimo, Yusuke; Koshiya, Shogo; Nagai, Takuro; Nito, Takehiro; Kimoto, Koji
Abstract: In this study, electron irradiation effects on lithium peroxide (Li2 O2 ), which is an important discharge product of Li–air (or Li–O2 ) batteries, were investigated using selected-area electron diffraction (SAED) and high-energy resolution electron energy-loss spectroscopy (EELS). The results obtained show that Li2 O2 to Li2 O transformation occurs with 80 and 300 keV incident electrons under high electron dose rates at 20 and −183 °C. The Li2 O2 to Li2 O transformation rate for 300 keV was 1/5 of that for 80 keV with the irradiation taking place at −183 °C. We also present a series of the EELS spectra that can be used as a criterion to judge the molar ratio of Li2 O to Li2 O2 in the general systems where Li2 O2 and Li2 O coexist.